Effect of Indoor Air Pollution on Chronic Obstructive Pulmonary Disease (COPD) Deaths in Southern Asia—A Systematic Review and Meta-Analysis - Shetty, Bellipady Shyam Prasad (Toxics, 2021)
Background: About half of the population in developing countries are exposed to indoor pollution such as combustion fuels at present. Chronic obstructive pulmonary disease (COPD) is one of the leading causes of mortality globally and the primary cause of COPD in women is indoor air pollution exposure, while tobacco smoking is the leading cause in men. The aim of this systematic review and meta-analysis is to evaluate the correlation between the indoor air pollution and deaths related to COPD and COPD prevalence in South Asia. Methods: A systematic search on studies with sufficient statistical power has been conducted from 1985 until 30 June 2020, in English electronic databases following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines in MEDLINE and PubMed databases with the terms Chronic Obstructive Pulmonary disease COPD or Chronic Bronchitis or Emphysema or COPD Deaths or Chronic Obstructive Lung Disease or Airflow Obstruction or Chronic Airflow Obstruction or Airflow Obstruction, Chronic or Bronchitis, Chronic and Mortality or Death or Deceased was conducted. Studies were eligible if they were Prospective controlled or non-controlled trials conducted in Southern Asia/ Asia and Retrospective studies conducted in Southern Asia/ Asia. Results: The results have concluded that long term exposure to indoor pollution had a significant effect on COPD deaths as well as its symptoms. Odd’s ratio was in a range of 1.05 (Randomized controlled trials) to 7.87 (Cross sectional studies) for all the studies mentioned. Meta-analysis observed a significantly higher Odds Ratio of 2.13 for COPD mortality and 2.08 for COPD prevalence on exposure to indoor air pollution. Conclusion: Exposure to solid fuel smoke is consistently and significantly correlated with COPD mortality and COPD prevalence in South Asian countries, in spite of heterogeneity observed in the studies included. For performing domestic tasks, initiatives are to be taken to reduce dependency on solid fuel by using cleaner alternatives or comparatively cleaner technology.